2013
DOI: 10.1039/c3cp00046j
|View full text |Cite
|
Sign up to set email alerts
|

Highly luminescent water-soluble quaternary Zn–Ag–In–S quantum dots for tumor cell-targeted imaging

Abstract: Exploring the synthesis and biomedical applications of biocompatible quantum dots (QDs) is currently one of the fastest growing fields of nanotechnology. Hence, in this work, we present a facile approach to produce water-soluble (cadmium-free) quaternary Zn-Ag-In-S (ZAIS) QDs. Their efficient photoluminescence (PL) emissions can be tuned widely in the range of 525-625 nm by controlling the size and composition of the QDs with the PL quantum yields (QYs) of 15-30%. These highly luminescent ZAIS QDs are less tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 40 publications
9
86
0
Order By: Relevance
“…ZZC does not contain cytotoxic elements (such as Cd and Se), thus the cytotoxicity of R8-ZZC to ASCs appears to be extremely suppressed in comparison to CdSe-based QDs18. The main cause appears to be due to the absence of toxicity elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZZC does not contain cytotoxic elements (such as Cd and Se), thus the cytotoxicity of R8-ZZC to ASCs appears to be extremely suppressed in comparison to CdSe-based QDs18. The main cause appears to be due to the absence of toxicity elements.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the development of novel QDs with extremely low cytotoxicity (especially Cd-free alternatives) is necessary for further advancement of QD technology15161718. There have been some reports about the cadmium-free QDs such as carbon or CuInS 2 /ZnS QDs192021.…”
mentioning
confidence: 99%
“…However, in 2011 Zhang and colleagues synthesized a quaternary QD system ZnAgInSe with PLQY of >70% . Then, two years later, Deng et al demonstrated the ability to maintain a PLQY as high as 50% while tuning ZnAgInSe QD emission from 660 to 800 nm in order to reach the NIR‐I region that is useful for in vivo imaging by varying the Zn:Ag precursor ratio . In 2017, Deng et al then used NIR‐I ZnAgInSe/ZnS quaternary core–shell QD nanoparticles with sulfobetaine‐poly(isobutylene‐ alt ‐maleic anhydride)–histimine (SPH) polymer conjugated on the surface for cancer imaging.…”
Section: Preclinical Quantum Dot Imaging In Cancermentioning
confidence: 99%
“…[137] As such, it is not surprising that there are examples of the hydrothermal synthesis of I-III-VI family semiconductor quantum dots. [138] In 2013, Deng et al synthesized ZnAgInS quantum dots with ab est quantum yield of~30 %b y boiling an aqueous solution of zinc acetate, silver nitrate, indium acetate with one of av ariety of sulfur precursors (thioacetamides, sodium sulfide,t hiourea,o rs odium thiosulfate) in presenceo fg lutathione as surface-passivatingr eagent. [138a] The glutathione ligands were later replaced with functionalized PEGs that allowed the materials to be conjugated to folic acid and RGD peptide.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%